Faktor yang Memfasilitasi Ibu dengan Kepatuhan yang Baik dalam Melaksanakan Empat Program Gizi Nasional di Indonesia: Facilitating Factors of Mothers’ Good Adherence to Four National Nutrition Programs in Indonesia - Wiradnyani, Luh Ade Ari; Khusun, Helda; Achadi, Endang L; Ocviyanti, Dwiana; Roshita, Airin (Amerta Nutrition, 2025)
Background: Mothers’ compliance with national nutrition programs during the first 1000 days of life is crucial to optimal child growth and development. However, national surveys have revealed low levels of compliance, suggesting challenges faced by mothers. Thus, understanding the facilitating factors of mother’s consistent good compliance is important. Objectives: To explore the facilitating factors of mothers’ good compliance with four national nutrition programs during the first 1000 days of life. Methos: Of the 48 mothers of 6-23-month-old children interviewed in this study, 10 demonstrated consistent compliance with the recommended maternal iron and folic acid (IFA) supplementation, breastfeeding, complementary feeding, and vitamin A capsule (VAC) supplementation programs. In-depth exploration and analysis were carried out on the 10 mothers, focusing on the roles of health staff, information exposure, knowledge, and family support. Results: All mothers had a strong initiative to seek information from various sources, including healthcare staff, the mother and child health book, and Internet (among urban mothers), irrespective of their socio-demographic backgrounds. Frequent information exposure resulted in good knowledge, except on VAC supplementation. Healthcare staff, particularly midwives, played significant roles in mothers’ compliance to IFA supplementation and breastfeeding, but much less for complementary feeding practices. The role of Posyandu cadres was limited to the dissemination of VAC supplementation schedules. Support from family members were observed in all programs, mainly in providing information and maintaining motivation. Conclusions: Information exposure and family support were key to mothers’ good compliance. The roles of healthcare staff, particularly in providing complementary feeding information, should be strengthened.